Skim siswa dalam menentukan akar dari persamaan kuadrat - Listyaningtyas, Alvia (Rekarta Academic Publisher, 2018)
Research qualitative deskripstif aims to understand skim students in determining roots of quadratic equations (QE). This Information is important for teachers to used as the basis of learning including in providing aid to students who do not be able to determining roots of QE. Subject in this research are 5 students class VIII junior high school and three students class XI senior high school. The result of this research shows that there are 4 skims who appeared in determining roots QE, namely skim pemfaktoran, skim manipulasi aljabar, skim rumus abc, and skim penyederhanaan dengan pembagian. The process of assimilating and accommodation are different. Inability to faced technical obstacles in use of a skim impact at an election the use of skim other.